Endoparasites of Wild Mammals Sheltered in Wildlife Hospitals and Rehabilitation Centres in Greece - Liatis, Theophanes K.; Monastiridis, Antonios A.; Birlis, Panagiotis; Prousali, Sophia; Diakou, Anastasia (Frontiers in Veterinary Science, 2017)
Wildlife parasitic diseases represent an important field of investigation as they may have a significant impact on wild animals’ health and fitness, and may also have zoonotic implications. The present study aimed to investigate the occurrence of endoparasites in wild mammals admitted to wildlife hospitals and rehabilitation centres in Greece. Sixty five animals belonging to 17 species and originated from various areas of continental and insular Greece were included in the survey. The most numerous animal species examined were hedgehogs (n=19), red foxes (n=16) and European roe deer (n=6). Faecal samples were collected individually and examined by floatation and sedimentation method. Parasites were found in 46 (70.7%) of the animals. Most parasites found in canids, felids and ruminants, are of great relevance to the domestic animals’ health and some of them are also of zoonotic importance. To the best of the author’s knowledge, this is the first report of endoparasites in hedgehogs, roe dears, fallow dears, badgers and bats, and the first report of the pulmonary nematode Troglostrongylus brevior in a wild cat in Greece. The significance of the parasites found in each animal species in regard to their health and their relevance to domestic animals and human health is discussed.